Personal pasts become academic presents: engaging reflexivity and considering dual insider/outsider roles in physical cultural fieldwork. Issue 3 (4th May 2021) - Hill, Teresa; Dao, Michael
ABSTRACT: When conducting qualitative research, researchers tend to find themselves closely connected to the participants in the field. This paper examines the complexities that existed for two researchers during time in the field conducting research closely related to their lived histories. Specifically, we consider the complicated dual role of insider/outsider that some researchers may occupy during field work when they 'return home' to a specific space or population that they did, or do, consider themselves to be a part of in order to conduct research. Through the use of vignettes, we detail the tensions that arose during the research process, discussing topics with which they were intimately connected. Additionally, this paper calls attention to important methodological concerns, considering the personal and public relationships at work in insider/outsider research, and examining the acute importance of reflexivity when the work requires a researcher to exist simultaneously as an insider/outsider. Our aim is to discuss the important, but complicated role of reflexivity as it is intricately woven into the field work, analysis, and personal process of research, specifically when the researcher is attempting to balance the roles of both insider and outsider perspectives.